2007
DOI: 10.1128/aem.02239-06
|View full text |Cite
|
Sign up to set email alerts
|

VanA-Type Enterococci from Humans, Animals, and Food: Species Distribution, Population Structure, Tn 1546 Typing and Location, and Virulence Determinants

Abstract: VanA-type human (n ‫؍‬ 69), animal (n ‫؍‬ 49), and food (n ‫؍‬ 36) glycopeptide-resistant enterococci (GRE) from different geographic areas were investigated to study their possible reservoirs and transmission routes. Pulsed-field gel electrophoresis (PFGE) revealed two small genetically related clusters, M39 (n ‫؍‬ 4) and M49 (n ‫؍‬ 13), representing Enterococcus faecium isolates from animal and human feces and from clinical and fecal human samples. Multilocus sequence typing showed that both belonged to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
48
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(63 citation statements)
references
References 61 publications
12
48
1
2
Order By: Relevance
“…The presence of indistinguishable vanA elements,mostly plasmid-borne, and virulence determinants in different species and PFGE-diverse populations suggested that all GRE might be potential reservoirs of resistance determinants and virulence traits transferable to human-adapted clusters. [25].…”
Section: Wwwintechopencommentioning
confidence: 99%
“…The presence of indistinguishable vanA elements,mostly plasmid-borne, and virulence determinants in different species and PFGE-diverse populations suggested that all GRE might be potential reservoirs of resistance determinants and virulence traits transferable to human-adapted clusters. [25].…”
Section: Wwwintechopencommentioning
confidence: 99%
“…Enterococci are commensal gut bacteria and as opportunistic pathogens, are capable of causing urogenital tract infections, endocarditis, meningitis, intra-abdominal abscesses, bacteremia, neonatal sepsis and nosocomial infections (5). Almost 20 species are in the genus Enterococcus, two of which (E.faecalis and E.feacium) are responsible for almost 90% of all Enterococcal infections in humans (5). The pathogenicity of Enterococci is affected by resistance to various antibiotics, rather than its virulence factors.…”
Section: Introductionmentioning
confidence: 99%
“…The antibacterial effects of garlic on different bacteria types has been reported (3,6). Enterococci are commensal gut bacteria and as opportunistic pathogens, are capable of causing urogenital tract infections, endocarditis, meningitis, intra-abdominal abscesses, bacteremia, neonatal sepsis and nosocomial infections (5). Almost 20 species are in the genus Enterococcus, two of which (E.faecalis and E.feacium) are responsible for almost 90% of all Enterococcal infections in humans (5).…”
Section: Introductionmentioning
confidence: 99%
“…ORT Ortopedia (BIAVASCO et al, 2007;FISHER et al, 2009;HIDRON et al, 2008;TEIXEIRA et al, 2007;TREITMAN et al, 2005;TSAI et al, 2005).…”
Section: Open Reading Frame (S)unclassified
“…As infecções enterocócicas ocorrem principalmente em pacientes imunodeprimidos ou debilitados, hospitalizados e incluem infecções intra-abdominais, do trato urinário, sepse hepatobiliares, bacteremia e endocardites, infecções de feridas cirúrgicas e sepse neonatal (FISHER et al, 2009;POH;TAN, 2006). Enterococos são a segunda causa mais comum de infecções nosocomiais da corrente sanguínea nos Estados Unidos e a resistência à vancomicina ocorre em aproximadamente um terço dos isolados (BIAVASCO et al, 2007;TSAI et al, 2005 A vancomicina atua inibindo a síntese da parede celular de bactérias sensíveis por meio da sua ligação de alta afinidade à extremidade terminal D-alanina-D-alanina de unidades precursoras da parede celular. Com isso, inibe a utilização dos substratos pela glicosiltransferase (uma enzima de síntese da parede celular) para produzir a cadeia de peptidoglicano nascente (CUI et al, 2006).…”
Section: Open Reading Frame (S)unclassified